2022
DOI: 10.1016/j.jbc.2021.101459
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular cathepsin Z signals through the α5 integrin and augments NLRP3 inflammasome activation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…Our previously published data on the anti‐inflammatory properties of HASC‐EVs 12 along with data in the literature, 21 prompted us to investigate whether HASC‐EVs could influence the activation of NLRP3 or AIM2‐inflammasome platform and IL‐1β maturation, using the human monocytic THP‐1 cell line, a well‐established cell model for the evaluation of inflammasome platform activation by different stimuli 24,33–35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previously published data on the anti‐inflammatory properties of HASC‐EVs 12 along with data in the literature, 21 prompted us to investigate whether HASC‐EVs could influence the activation of NLRP3 or AIM2‐inflammasome platform and IL‐1β maturation, using the human monocytic THP‐1 cell line, a well‐established cell model for the evaluation of inflammasome platform activation by different stimuli 24,33–35 …”
Section: Resultsmentioning
confidence: 99%
“…Our previously published data on the anti-inflammatory properties of HASC-EVs 12 along with data in the literature, 21 prompted us to investigate whether HASC-EVs could influence the activation of NLRP3 or AIM2-inflammasome platform and IL-1β maturation, using the human monocytic THP-1 cell line, a well-established cell model for the evaluation of inflammasome platform activation by different stimuli. 24,[33][34][35] To this aim, THP-1 cells were pre-treated with either HASC-P10-or HASC-P100 (100 µg/ml) for 1 h, before being stimulated with the inflammasome activating stimuli LPS (10 μg/ml, 20 min) and ATP (5 mM, 40 min) (LPS + ATP) 21,34,35 ; control cells were left untreated or treated with either type of EVs alone. We found that HASC-P10 or HASC-P100 pre-treatment prevented both the activation of the NLRP3/caspase-1/inflammasome platform and IL-1β maturation after LPS and ATP treatment (Figure 5).…”
Section: Hasc-evs Prevent Inflammasome Activation In Thp-1 Cellsmentioning
confidence: 99%
“…Ctsz is a member of the lysosomal cysteine cathepsin protease family, which comprises 11 members in humans [47]. In the context of neuroinflammation, Ctsz has been implicated in the development of inflammation, Interleukin-1β (IL-1β) production, and NLR Family Pyrin Domain Containing 3 (NLRP3)-inflammasome activation [49, 50]. We measured Ctsz levels to further evaluate the effects of UA in AD brains by ELISA.…”
Section: Resultsmentioning
confidence: 99%
“…CTSZ is associated with neurodegenerative diseases like AD and Huntington’s disease (HD) [51, 52] and is related to inflammation and Interleukin-1β (IL-1β) production [50]. We next examined the mRNA expression level of IL-1β and IL-6 in the hippocampus to assess the effects of UA on inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Although silicosis is an old disease, our understanding of the disease pathogenesis is limited and no effective treatment is currently available. Over the past two decades, silica has been shown to be a potent activator of the NLRP3 inflammasome, which is a molecular platform mediating either the maturation of inflammatory factors (such as IL-1β and IL-18) or inflammatory cell death (pyroptosis) 31 , 64 , 65 . Increasing evidence confirmed that NLRP3 inflammasome-mediated chronic inflammation participates in the development of silicosis 6 .…”
Section: Discussionmentioning
confidence: 99%